Socio-economic profile, technologies adoption and constraints of traditional Hariana cattle rearing farmers in its breeding tract - Prasad, Kotresh; Singh, Man; Lathwal, Surender Singh (Indian Journal of Dairy Science, 2023)
The study was conducted in Hisar, Bhiwani, Rohtak and Jhajjar districts of Haryana state in India to assess the socioeconomic profile, technology adoption and constraints of the farmers rearing Hariana cattle in its breeding tract. A total of 240 respondents (60 respondents from each district) were purposively selected and interviewed individually. 84.58 % of the farmers belong to joint family. Occupation of majority of the respondents was agriculture (53.33 %) along with dairying. Most of the farmers were small (27.50 %), marginal (28.34 %) and landless (29.58 %) with an average land holding of 2.6 acres. 50 % of them belong to medium (40000-150000 lakhs) annual family income group. The average herd size and lactation yield of Hariana cattle in study area was 1.56 and 1014.21 L respectively. Majority of the farmers have adopted almost all the technologies even though rest of them have not adopted due to lack of knowledge and other constraints. The major constraints in Hariana cattle rearing is low productivity compared to Murrah buffalo and CB cattle. The other prevailing constraints of farmers in the study areas were aggressive behaviour of Hariana cattle, sale of male calves, reduction in grazing land, lack of timely veterinary and AI services, dilution of breed arise from indiscriminate breeding and scarcity of feed and fodder.